aboutsummaryrefslogtreecommitdiff
path: root/assignment2.tex
diff options
context:
space:
mode:
Diffstat (limited to 'assignment2.tex')
-rw-r--r--assignment2.tex112
1 files changed, 112 insertions, 0 deletions
diff --git a/assignment2.tex b/assignment2.tex
new file mode 100644
index 0000000..fa70c40
--- /dev/null
+++ b/assignment2.tex
@@ -0,0 +1,112 @@
+\documentclass[10pt,a4paper]{article}
+
+\usepackage[margin=2cm]{geometry}
+
+\usepackage{enumitem}
+\setenumerate[1]{label=\arabic*.}
+\setenumerate[2]{label=(\alph*)}
+
+% textcomp package is not available everywhere, and we only need the Copyright symbol
+% taken from http://tex.stackexchange.com/a/1677/23992
+\DeclareTextCommandDefault{\textregistered}{\textcircled{\check@mathfonts\fontsize\sf@size\z@\math@fontsfalse\selectfont R}}
+
+\usepackage{fancyhdr}
+\renewcommand{\headrulewidth}{0pt}
+\renewcommand{\footrulewidth}{0pt}
+\fancyhead{}
+\fancyfoot[C]{Copyright {\textcopyright} 2015 Camil Staps}
+\pagestyle{fancy}
+
+\usepackage{amsmath}
+\usepackage{amsfonts}
+
+\parindent0pt
+
+\title{Calculus en Kansrekenen - assignment 2}
+\author{Camil Staps\\\small{s4498062, group Bram}}
+
+\begin{document}
+
+\maketitle
+\thispagestyle{fancy}
+
+\begin{enumerate}
+ \item \begin{enumerate}
+ \item $$\lim\limits_{x\to-\infty}\frac{x^3+2x^2+2}{3x^3+x+4} = \lim\limits_{x\to-\infty}\frac{1+\frac2x+\frac2{x^3}}{3+\frac1x+\frac4{x^3}} = \frac13.$$
+ \item $$\lim\limits_{x\to\infty}\frac{3x^2+8}{x+1}=\frac{3x+\frac8x}{1+\frac1x}=\lim\limits_{x\to\infty}3x+\frac8x=\lim\limits_{x\to\infty}3x=\infty.$$
+ \item $$\lim\limits_{x\to\infty}\frac{2x+1}{x^2+x}=\lim\limits_{x\to\infty}\frac{\frac2x+\frac1{x^2}}{1+\frac1x}=\frac01=0.$$
+ \item \begin{align*}
+ & \lim\limits_{x\to a}\frac{x^n-a^n}{x-a}\\
+ = & \lim\limits_{a+h\to a}\frac{(a+h)^n-a^n}{a+h-a}\qquad\text{with $h=x-a$}\\
+ = & \lim\limits_{h\to0}\frac{(a+h)^n - a^n}{h}\\
+ = & \left(a^n\right)'\\
+ = & n\cdot a^{n-1}.
+ \end{align*}
+ \end{enumerate}
+
+ \item \begin{enumerate}
+ \item $$f'(2) = \lim\limits_{h\to0}\frac{f(2+h)-f(2)}{h}=\lim\limits_{h\to0}\frac0h=0.$$
+ \item $$f'(x) = \lim\limits_{h\to0}\frac{f(x+h)-f(x)}{h} = \lim\limits_{h\to0}\frac{2(x+h)+3-(2x+3)}{h} = \lim\limits_{h\to0}2 = 2.$$
+ \item $$f'(3) = \lim\limits_{h\to0}\frac{f(3+h)-f(3)}{h} = \lim\limits_{h\to0}\frac{h^2+6h+9+6+2h+1-(9+6+1)}{h} = \lim\limits_{h\to0}h+8=8.$$
+ \item \begin{align*}
+ f'(x) &= \lim\limits_{h\to0}\frac{f(x+h)-f(x)}{h}\\
+ &= \lim\limits_{h\to0}\frac{\frac{5(x+h)-7}{4(x+h)+3} - \frac{5x-7}{4x+3}}{h}\\
+ &= \lim\limits_{h\to0}\frac{\frac{43h}{(4x+4h+3)(4x+3)}}{h}\\
+ &= \lim\limits_{h\to0}\frac{43}{(4x+4h+3)(4x+3)}\\
+ &= \frac{43}{(4x+3)^2}.
+ \end{align*}
+ \end{enumerate}
+
+ \item \begin{enumerate}
+ \item We rewrite this to something of the form $y=ax+b$:
+
+ \begin{align*}
+ 4y - x + 2(1-\ln2) &= 0\\
+ 4y &= x - 2(1-\ln2)\\
+ y &= \frac14x - \frac12(1-\ln2)
+ \end{align*}
+
+ For a line $y=ax+b$, $a$ is the slope, so in this case we have the slope $\frac14$.
+
+ \item We equate $f(x)$ and $y$ for $x=2$:
+
+ \begin{align*}
+ \frac14\cdot2 - \frac12(1-\ln2) &= a\ln2 \\
+ \frac12\ln2 &= a\ln2 \\
+ a &= \frac12.
+ \end{align*}
+
+ \item For the slope we take the derivative of $f$, i.e. $f'(x) = \frac ax = \frac12a$.
+
+ Then as intercept we take $f(2)-2\cdot f'(2) = a\ln2 - 2\cdot\frac a2 = a\ln2-a$.
+
+ The tangent line is then $y=\frac12ax+a\ln2-a$.
+ \end{enumerate}
+
+ \item \begin{enumerate}
+ \item $f'(x) = 4x^3-6x^2.$
+ \item $f'(x) = \frac{(x-7)(2x)-(x^2+5)(1)}{(x-7)^2} = \frac{x+2}{x-7}.$
+ \item \begin{align*}
+ f'(x) &= \left(\sin{\sqrt x}\cdot\sin{\sqrt x}\right) \\
+ &= 2\cdot\sin\sqrt x\cdot\left(\sin\sqrt x\right)' \\
+ &= 2\cdot\sin\sqrt x\cdot\cos\sqrt x\cdot\frac12\cdot x^{-\frac12} \\
+ &= \frac12\sin\left(2\sqrt x\right)\cdot\frac1{\sqrt x} \\
+ &= \frac{\sin\left(2\sqrt x\right)}{2\sqrt x}.
+ \end{align*}
+ \item %todo
+ \item $f'(x) = \left(e^{\tan x}\right)' = e(\tan x)\cdot\tan'x = \frac{e(\tan x)}{\cos^2x}$.
+ \item $f'(x) = -\frac1{\cos x}\cdot-\sin x=\frac{\sin x}{\tan x}$.
+ \item \begin{align*}
+ f'(x) &= \frac1{\sqrt{1-(1-2x)^2}}\cdot-2 \\
+ &= -2\cdot\frac1{\sqrt{4x^2+4x}} \\
+ &= -2\cdot\frac1{2\sqrt{x^2+x}} \\
+ &= -\left(x^2+x\right)^{-\frac12}.
+ \end{align*}
+ \item %todo
+ \end{enumerate}
+
+ \item % todo
+\end{enumerate}
+
+\end{document}
+